2006
DOI: 10.2975/29.2006.197.204
|View full text |Cite
|
Sign up to set email alerts
|

What's in a service? Consumers' views of Australian mental health services.

Abstract: This paper reports on a series of interviews with consumers of mental health services, conducted as part of the Consumer Evaluation of Mental Health Services project (CEO-MHS). With one of our overarching aims being to develop a consumer oriented and consumer directed method of evaluating mental health services, we considered seeking consumers' views of mental health services, using qualitative interviews, to be essential. Consumer Researchers from the team conducted 33 interviews in NSW, Australia. Eleven the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 17 publications
1
16
0
1
Order By: Relevance
“…Overall, prior literature, theoretical explanations and historical perspectives present a variety of data regarding the lived experience of mental disorders, depending on the diverse study objectives, culture and backgrounds and structures of the health care systems (Andersen & Larsen, 2012;Borg & Davidson, 2008;De Maynard, 2007;Hirschfeld et al, 2005;Jönsson et al, 2008;Lee et al, 2007;Liu et al, 2012;McCann & Clark, 2004;Moreira & Coelho, 2003;Nyström & Nyström, 2007;Nyström et al, 2002;Pollack & Aponte, 2001;Sanseeha et al, 2009;Schön, 2009;Thompson et al, 2008;Wang, 2011;Ward, 2011). Moreover, it is through metasynthesis that we can achieve greater understanding of the core of these experiences and shed some light on the phenomenon of SMI and suffering in its fundamental nature (Allen, Carpenter, Sheets, Miccio, & Ross, 2003;Barker & Buchanan-Barker, 2011;Barkham, 2002;Davies, 2014;Day et al, 2005;Deegan & Drake, 2006;Happell, Manias, & Roper, 2004;Hewitt & Coffey, 2005;Kieft, de Brouwer, Francke, & Delnoij, 2014;Kopelowicz & Liberman, 2003;Määttä, 2006;Malins, Oades, Viney, & Aspden, 2006;McCabe, 2004;Mueser et al, 2002;Yu & Kirk, 2008).…”
Section: Introductionmentioning
confidence: 95%
“…Overall, prior literature, theoretical explanations and historical perspectives present a variety of data regarding the lived experience of mental disorders, depending on the diverse study objectives, culture and backgrounds and structures of the health care systems (Andersen & Larsen, 2012;Borg & Davidson, 2008;De Maynard, 2007;Hirschfeld et al, 2005;Jönsson et al, 2008;Lee et al, 2007;Liu et al, 2012;McCann & Clark, 2004;Moreira & Coelho, 2003;Nyström & Nyström, 2007;Nyström et al, 2002;Pollack & Aponte, 2001;Sanseeha et al, 2009;Schön, 2009;Thompson et al, 2008;Wang, 2011;Ward, 2011). Moreover, it is through metasynthesis that we can achieve greater understanding of the core of these experiences and shed some light on the phenomenon of SMI and suffering in its fundamental nature (Allen, Carpenter, Sheets, Miccio, & Ross, 2003;Barker & Buchanan-Barker, 2011;Barkham, 2002;Davies, 2014;Day et al, 2005;Deegan & Drake, 2006;Happell, Manias, & Roper, 2004;Hewitt & Coffey, 2005;Kieft, de Brouwer, Francke, & Delnoij, 2014;Kopelowicz & Liberman, 2003;Määttä, 2006;Malins, Oades, Viney, & Aspden, 2006;McCabe, 2004;Mueser et al, 2002;Yu & Kirk, 2008).…”
Section: Introductionmentioning
confidence: 95%
“…User involvement has received attention at service and strategic levels in developed countries (Baggott & Forster, 2008;Boardman, 2005;HASCAS, 2005;Linhorst, Eckert, Hamilton, & Young, 2001;Malins, Oaders, Viney, & Aspden, 2006;McClean, 1995;Peck, Gulliver, & Towel, 2002), but less so in developing countries (Katontoka, 2007;Ntulo, 2006;Underhill, 2005), including South Africa.…”
Section: Introductionmentioning
confidence: 97%
“…Research has found that consumer relationships with providers have a bearing on medication adherence. Consumers want providers to listen to, and respect, their views around medication (Allen, Carpenter, Sheets, Miccio, & Ross, 2003;Day et al, 2005;Happell, Manias, & Roper, 2004;Malins, Oades, Viney, & Aspden, 2006). Other studies underline the need for collaboration between consumers and providers, and for consumer training, so that they will be able to participate more fully in treatment decisions (Deegan & Drake, 2006;Kopelowicz & Liberman, 2003;Mueser et al, 2002).…”
Section: Recovery and New Approaches To Medicationmentioning
confidence: 99%